MALPRAKTEK DALAM PENYELENGGARAAN PEMILU ANGGOTA DPRD KABUPATEN WAROPEN TAHUN 2019 (STUDI KASUS TENTANG PELAKSANAAN REKAPITULASI HASIL PENGHITUNGAN PEROLEHAN SUARA TINGKAT KABUPATEN) - Karel Wopari; Yosephina Ohoiwutun (Universitas Cenderawasih, 2021)
Election is a democratic party that guarantees freedom, justice and equality for individuals in determining leaders in the executive and legislative fields. In every stage of the election process, there must be opportunities for problems, errors and violations such as violence, buying and selling of votes, and manipulation. It is undeniable that violations that include manipulation of election regulations, voter choice and electoral administration in the implementation of the recapitulation of the results of the vote count at the district level, still color the implementation of elections. The purpose of this study is to find out, analyze and describe the forms and factors that influence electoral malpractice in the recapitulation of the results of the calculation of the votes acquired by the candidates for members of the Waropen Regency DPRD at the district level in the 2019 Election. The research method uses a qualitative descriptive approach. Collecting data using in-depth interview techniques and active observation. Research informants are Election Organizers and Secretariats and Election Contestants. Data analysis techniques through the stages of preparation, codification, topic description, and data presentation. The results of the study indicate that there were electoral malpractice actions that occurred before and during the recapitulation of the results of the counting of district-level votes in the Election for Candidates for Members of the Waropen Regency DPRD in 2019 in the form of manipulation of voter choices and manipulation of electoral administration. Factors that influence the occurrence of electoral malpractice are the negligence of the election organizers and the existence of vote buying by election participants (candidates) against the election organizers